Ambisonics Sound Source Localization With Varying Amount of Visual Information in Virtual Reality - Huisman, Thirsa; Ahrens, Axel; MacDonald, Ewen (Frontiers in Virtual Reality, 2021)
To reproduce realistic audio-visual scenarios in the laboratory, ambisonics is often used to reproduce a sound field over loudspeakers and virtual reality (VR) glasses are used to present visual information. Both technologies have been shown to be suitable for research. However, the combination of both technologies, ambisonics and VR glasses, might affect the spatial cues for auditory localization and thus, the localization percept. Here, we investigated how VR glasses affect the localization of virtual sound sources on the horizontal plane produced using either 1st, 3rd, 5th or 11th order ambisonics with and without visual information. Results showed that with 1st order ambisonics the localization error is larger than with the higher orders, while the differences across the higher orders were small. The physical presence of the VR glasses without visual information increased the perceived lateralization of the auditory stimuli by on average about 2°, especially in the right hemisphere. Presenting visual information about the environment and potential sound sources did reduce this HMD-induced shift, however it could not fully compensate for it. While the localization performance itself was affected by the ambisonics order, there was no interaction between the ambisonics order and the effect of the HMD. Thus, the presence of VR glasses can alter acoustic localization when using ambisonics sound reproduction, but visual information can compensate for most of the effects. As such, most use cases for VR will be unaffected by these shifts in the perceived location of the auditory stimuli.